Comparative Study During Pandemic Between Conventional Construction System and Industrial Building System (IBS) on Workers and Costs in Batu Pahat, Johor - Neemat, Siti 'Aisyah; Tami, Hannifah (Recent Trends in Civil Engineering and Built Environment, 2023)
Majority of construction methods that are often used in Malaysia are conventional construction methods and Industrial Building System (IBS) construction methods. Both of these methods have their respective advantages and disadvantages that give impact in construction during a pandemic especially in terms of costs construction and workers. This study aims to analysis the more effective construction methods in terms of construction workers and construction costs, as well as to identify the impact that occurs on construction during a pandemic. This study uses a combination of quantitative and qualitative methods. The analysis of the study was done by analyzing the respondents' data given through a questionnaire using Service Package for Science Social (SPSS) and descriptive system while the observation method (interview) was done on the project engineer. The results of the study found that the most effective construction method during a pandemic is the IBS method. Moreover, the majority of respondents agree that the impact of the pandemic on the construction sector was that the cost and duration of construction increased, and the shortage of workers. Finally, the study also found some recommendations that need to be made to improve the construction sector during a pandemic.